First description of the karyotype and localization of major and minor ribosomal genes in Rhoadsia altipinna Fowler, 1911 (Characiformes, Characidae from Ecuador) - Sánchez Romero, Omar; Quezada Abad, César; Quizhpe, Patricio; Cordero Nirchio, Mauro (My University, 2015)
Karyotypic fearures of Rhoadsia altipinna Fowler, 1911 from Ecuador were investigated by examining meraphase chromosornes rhrough Gicmsa staining, C-banding, Ag-NOR, and rwo-color-fluorescence in situ hybridization (FISH) far mapping of l BS and 5S ribosomal genes. The species exhibir a karyotype wirh 2n 50, cornposed of 1 O metacentric, 26 submeracentric and 14 subtelocentric elements, with a fundamental number FN=86 and is characterized by the presence of a larger rnetacentric pair (number 1), which is abour 2/3 longer than the average lengrh of the rest of rhe rnetacenrric series. Sex chromosomes were nor observed. Hererochromarin is idcntifiable on 44 chromosomcs, disrribuced in paraccnrromeric position near rhe centrornere. The firsr meracentric pair presents rwo well-defined hetercchrornaríc blocks in paracenrrornerlc posirion, near che centromere, Impregnation with silver nitrare showcd a single pair of Ag-posltíve NORs localized ar terminal regions of the shorc arrns of rhe subrelocentric chrornosome pair number 12. FISH assay confirmed these localization of NORs and revealed thar minar rDNA clusters occur interstirially on the largcr metacentric pair number. Comparison of results here reponed witb those available on other.
Keywords: RIBOSOMAL; GENES; COMPARATIVA CYTOGENETICS